Konsep Dialog Agama Menurut Paul F. Kniter dan Implikasinya bagi Hubungan Antar Umat Beragama di Kabupaten Fak-Fak - Ngabalin, Marthinus; Lattu, Izak Y. M.; Listyani, Listyani (KENOSIS: Jurnal Kajian Teologi, 2024)
This study aims to describe the application of the concept of religious dialogue according to Paul F Knitter and explain the implications of the application of the concept of religious dialogue for interfaith relations in Fakfak Regency. The participants of this study were 10 respondents. data were collected using qualitative design and data collection methods were interview and literature study. The findings of this study showed that the emergence of dialogues in Fakfak society contributed to the social diversity based on the history of Fakfak society. On the other hand, however, this writing gives emphasis to the perspective on religion. Therefore, the important point is how the society encourages interfaith dialogue and how each religious community places other communities equally in dialogue spaces.